A novel trigger based on neural networks for radio neutrino detectors - Anker, Astrid; Paul, Manuel P.; Baldi, Pierre; Barwick, Steven W.; Beise, Jakob; Bernhoff, Hans; Besson, Dave Z.; Bingefors, Nils; Cataldo, Maddalena; Chen, Pisin; Fernández, Daniel García; Gaswint, Geoffrey; et al. (Proceedings of Science, 2022)
The ARIANNA experiment is a proposed Askaryan detector designed to record radio signals induced by neutrino interactions in the Antarctic ice. Because of the low neutrino flux at high energies, the physics output is limited by statistics. Hence, an increase in sensitivity significantly improves the interpretation of data and offers the ability to probe new parameter spaces. The trigger thresholds are limited by the rate of triggering on unavoidable thermal noise fluctuations. The real-time thermal noise rejection algorithm enables the thresholds to be lowered substantially and increases the sensitivity by up to a factor of two compared to the current ARIANNA capabilities. A deep learning discriminator, based on a Convolutional Neural Network (CNN), is implemented to identify and remove a high percentage of thermal events in real time while retaining most of the neutrino signals. We describe a CNN that runs on the current ARIANNA microcomputer and retains 95% of the neutrino signals at a thermal rejection factor of 105. Finally, the experimental verification from lab measurements are conducted.
CRIS-Team Scopus Importer:2023-08-15

Developing new analysis tools for near surface radio-based neutrino detectors - Anker, A.; Baldi, P.; Barwick, S.; Beise, J.; Besson, D.; Chen, P.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hanson, J.; Klein, S.; Kleinfelder, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2023)
The ARIANNA experiment is an Askaryan radio detector designed to measure high-energy neutrino induced cascades within the Antarctic ice. Ultra-high-energy neutrinos above 1016 eV have an extremely low flux, so experimental data captured at trigger level need to be classified correctly to retain as much neutrino signal as possible. We first describe two new physics-based neutrino selection methods, or “cuts”, (the updown and dipole cut) that extend the previously published analysis to a specialized ARIANNA station with 8 antenna channels, which is double the number used in the prior analysis. For a standard trigger with a threshold signal to noise ratio at 4.4, the new cuts produce a neutrino efficiency of > 95% per station-year of operation, while rejecting 99.93% of the background (corresponding to 53 remaining experimental background events). When the new cuts are combined with a previously developed cut using neutrino waveform templates, all background is removed at no change of efficiency. In addition, the neutrino efficiency is extrapolated to 1,000 station-years of operation, obtaining 91%. This work then introduces a new selection method (the deep learning cut) to augment the identification of neutrino events by using deep learning methods and compares the efficiency to the physics-based analysis. The deep learning cut gives 99% signal efficiency per station-year of operation while rejecting 99.997% of the background (corresponding to 2 remaining experimental background events), which are subsequently removed by the waveform template cut at no significant change in efficiency. The results of the deep learning cut were verified using measured cosmic rays which shows that the simulations do not introduce artifacts with respect to experimental data. The paper demonstrates that the background rejection and signal efficiency of near surface antennas meets the requirements of a large scale future array, as considered in baseline design of the radio component of IceCube-Gen2.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Machine learning; neutrino astronomy; neutrino detectors; ultra high energy photons and neutrinos

Development of an in-situ calibration device of firn properties for Askaryan neutrino detectors - Anker, Astrid; Baldi, Pierre; Barwick, Steven W.; Beise, Jakob; Bernhoff, Hans; Besson, Dave Z.; Bingefors, Nils; Cataldo, Maddalena; Chen, Pisin; Fernández, Daniel García; Gaswint, Geoffrey; Glaser, Christian; et al. (Proceedings of Science, 2022)
High energy neutrinos (E >1017 eV) are detected cost-efficiently via the Askaryan effect in ice, where a particle cascade induced by the neutrino interaction produces coherent radio emission that can be picked up by antennas installed below the surface. A good knowledge of the near surface ice (aka firn) properties is required to reconstruct the neutrino properties. In particular, a continuous monitoring of the snow accumulation (which changes the depth of the antennas) and the index-of-refraction profile are crucial for an accurate determination of the neutrino’s direction and energy. We present an in-situ calibration system that extends the radio detector station with a radio emitter to continuously monitor the firn properties by measuring time differences of direct and reflected (off the surface) signals (D’n’R). We optimized the station layout in a simulation study and quantified the achievable precision. We present 14 months of data of the ARIANNA detector on the Ross Ice Shelf, Antarctica, where a prototype of this calibration system was successfully used to monitor the snow accumulation with unprecedented precision of 1 mm. We explore and test several algorithms to extract the D’n’R time difference from noisy data (including deep learning). This constitutes an in-situ test of the neutrino vertex distance reconstruction using the D’n’R technique which is needed to determine the neutrino energy.
CRIS-Team Scopus Importer:2023-08-15

In situ, broadband measurement of the radio frequency attenuation length at Summit Station, Greenland - Aguilar, J. A.; Allison, P.; Beatty, J. J.; Besson, D.; Bishop, A.; Botner, O.; Bouma, Sjoerd; Buitink, S.; Cataldo, Maddalena; Clark, B. A.; Curtis-Ginsberg, Z.; Connolly, A.; et al. (Journal of Glaciology, 2022)
Over the last 25 years, radiowave detection of neutrino-generated signals, using cold polar ice as the neutrino target, has emerged as perhaps the most promising technique for detection of extragalactic ultra-high energy neutrinos (corresponding to neutrino energies in excess of 0.01 Joules, or 10(17) electron volts). During the summer of 2021 and in tandem with the initial deployment of the Radio Neutrino Observatory in Greenland (RNO-G), we conducted radioglaciological measurements at Summit Station, Greenland to refine our understanding of the ice target. We report the result of one such measurement, the radio-frequency electric field attenuation length L-alpha. We find an approximately linear dependence of L-alpha on frequency with the best fit of the average field attenuation for the upper 1500 m of ice: < L-alpha > = ((1154 +/- 121) - (0.81 +/- 0.14) (v/MHz)) m for frequencies v is an element of [145 - 3501 MHz.
CRIS-Team WoS Importer:2022-06-10

Measuring the polarization reconstruction resolution of the ARIANNA neutrino detector with cosmic rays - Anker, A.; Baldi, P.; Barwick, S. W.; Beise, J.; Besson, D. Z.; Bouma, Sjoerd; Cataldo, Maddalena; Chen, P.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hallmann, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2022)
The ARIANNA detector is designed to detect neutrinos with energies above 1017 eV. Due to the similarities in generated radio signals, cosmic rays are often used as test beams for neutrino detectors. Some ARIANNA detector stations are equipped with antennas capable of detecting air showers. Since the radio emission properties of air showers are well understood, and the polarization of the radio signal can be predicted from the arrival direction, cosmic rays can be used as a proxy to assess the reconstruction capabilities of the ARIANNA neutrino detector. We report on dedicated efforts of reconstructing the polarization of cosmic-ray radio pulses. After correcting for difference in hardware, the two stations used in this study showed similar performance in terms of event rate and agreed with simulation. Subselecting high quality cosmic rays, the polarizations of these cosmic rays were reconstructed with a resolution of 2.5° (68% containment), which agrees with the expected value obtained from simulation. A large fraction of this resolution originates from uncertainties in the predicted polarization because of the contribution of the subdominant Askaryan effect in addition to the dominant geomagnetic emission. Subselecting events with a zenith angle greater than 70° removes most influence of the Askaryan emission, and, with limited statistics, we found the polarization uncertainty is reduced to 1.3° (68% containment).
CRIS-Team Scopus Importer:2022-05-13
Keywords: cosmological neutrinos; neutrino astronomy; neutrino detectors; ultra high energy photons and neutrinos

Polarization Reconstruction of Cosmic Rays with the ARIANNA Neutrino Radio Detector - Zhao, Leshan; Anker, Astrid; Baldi, Pierre; Barwick, Steven W.; Beise, Jakob; Bernhoff, Hans; Besson, Dave Z.; Bingefors, Nils; Cataldo, Maddalena; Chen, Pisin; Fernández, Daniel García; Gaswint, Geoffrey; et al. (Proceedings of Science, 2022)
The ARIANNA detector is designed to detect neutrinos of energies above 1016 eV. Due to the similarities in generated radio signals, cosmic rays are often used as test beams for neutrino detectors. Some ARIANNA detector stations are equipped with antennas capable of detecting air showers. The radio emission properties of air showers are well understood, and the polarization of the radio signal can be predicted from arrival direction with high precision. For this reason, cosmic rays can be used as a proxy to assess the reconstruction capabilities of the ARIANNA neutrino detector. We report on dedicated efforts of reconstructing the polarization of cosmic-ray radio pulses. A total of 148 cosmic rays are identified from over 90,000 triggered events collected between Nov 21, 2018 and Mar 15, 2019. A cut was put on these events requiring them to have a signal-to-noise (SNR) ratio of at least 4.5 in all upward-facing channels. This was to improve the performance of arrival direction and polarization reconstruction algorithms. Polarization of these cosmic rays were reconstructed with a resolution of 3.5 degrees (68% containment), which agrees with the expected value we obtained from simulation. Furthermore, if we subselect events with zenith angle greater than 70 deg, the contribution to polarization of Askaryan effect is reduced, which reduces the error in the predicted polarization. With limited statistics, we find the polarization uncertainty is reduced to 1.3 deg (68% containment).
CRIS-Team Scopus Importer:2023-08-15

Radiofrequency ice dielectric measurements at Summit Station, Greenland - Aguilar, Juan Antonio; Allison, Patrick; Besson, Dave; Bishop, Abby; Botner, Olga; Bouma, Sjoerd; Buitink, Stijn; Cataldo, Maddalena; Clark, Brian A.; Couberly, Kenny; Curtis-Ginsberg, Zach; Dasgupta, Paramita; et al. (Journal of Glaciology, 2023)
We recently reported on the radio-frequency attenuation length of cold polar ice at Summit Station, Greenland, based on bi-static radar measurements of radio-frequency bedrock echo strengths taken during the summer of 2021. Those data also allow studies of (a) the relative contributions of coherent (such as discrete internal conducting layers with sub-centimeter transverse scale) vs incoherent (e.g. bulk volumetric) scattering, (b) the magnitude of internal layer reflection coefficients, (c) limits on signal propagation velocity asymmetries ('birefringence') and (d) limits on signal dispersion in-ice over a bandwidth of ∼100 MHz. We find that (1) attenuation lengths approach 1 km in our band, (2) after averaging 10 000 echo triggers, reflected signals observable over the thermal floor (to depths of ∼1500 m) are consistent with being entirely coherent, (3) internal layer reflectivities are ≈-60-70 dB, (4) birefringent effects for vertically propagating signals are smaller by an order of magnitude relative to South Pole and (5) within our experimental limits, glacial ice is non-dispersive over the frequency band relevant for neutrino detection experiments.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Arctic glaciology; ice physics; radio-echo sounding

Reconstructing the arrival direction of neutrinos in deep in-ice radio detectors - Plaisier, Ilse; Bouma, Sjoerd; Nelles, Anna (European Physical Journal C: Particles and Fields, 2023)
In-ice radio detectors are a promising tool for the discovery of EeV neutrinos. For astrophysics, the implications of such a discovery will rely on the reconstruction of the neutrino arrival direction. This paper describes a first complete neutrino arrival direction reconstruction for detectors employing deep antennas such as RNO-G or planning to employ them like IceCube-Gen2. We will didactically introduce the challenges of neutrino direction reconstruction using radio emission in ice, elaborate on the detail of the algorithm used, and describe the obtainable performance based on a simulation study and discuss its implication for astrophysics.
CRIS-Team Scopus Importer:2023-07-14

Reconstructing the neutrino energy for in-ice radio detectors: A study for the Radio Neutrino Observatory Greenland (RNO-G) - Aguilar, J. A.; Allison, P.; Beatty, J. J.; Bernhoff, H.; Besson, D.; Bingefors, N.; Botner, O.; Bouma, Sjoerd; Buitink, S.; Carter, K.; Cataldo, Maddalena; Clark, B. A.; et al. (European Physical Journal C: Particles and Fields, 2022)
Since summer 2021, the Radio Neutrino Observatory in Greenland (RNO-G) is searching for astrophysical neutrinos at energies > 10 PeV by detecting the radio emission from particle showers in the ice around Summit Station, Greenland. We present an extensive simulation study that shows how RNO-G will be able to measure the energy of such particle cascades, which will in turn be used to estimate the energy of the incoming neutrino that caused them. The location of the neutrino interaction is determined using the differences in arrival times between channels and the electric field of the radio signal is reconstructed using a novel approach based on Information Field Theory. Based on these properties, the shower energy can be estimated. We show that this method can achieve an uncertainty of 13% on the logarithm of the shower energy after modest quality cuts and estimate how this can constrain the energy of the neutrino. The method presented in this paper is applicable to all similar radio neutrino detectors, such as the proposed radio array of IceCube-Gen2.
CRIS-Team Scopus Importer:2022-03-04

Science Case and Detector Concept for the ARIANNA High Energy Neutrino Telescope at Moore’s Bay, Antarctica - Barwick, Steven W.; Anker, Astrid; Baldi, Pierre; Beise, Jakob; Bernhoff, Hans; Besson, Dave Z.; Bingefors, Nils; Cataldo, Maddalena; Chen, Pisin; Fernández, Daniel García; Gaswint, Geoffrey; Glaser, Christian; et al. (Proceedings of Science, 2022)
The ARIANNA neutrino detector, located at sea-level on the Ross Ice Shelf, Antarctica, consists of 200 autonomous and independent detector stations separated by 1 kilometer in a uniform triangular mesh, and serves to inform the planning of the future projects. The primary science mission of ARIANNA is to search for sources of neutrinos with energies greater than 1017 eV, complementing the reach of IceCube and other neutrino telescopes that focus on lower energies. An ARIANNA observation of a neutrino source would provide strong insight into the enigmatic sources of cosmic rays. ARIANNA observes the radio emission from high energy neutrino interactions in the Antarctic ice. Among radio based concepts under current investigation, ARIANNA would uniquely survey the vast majority of the southern sky at any instant in time, and an important region of the northern sky, by virtue of its location on the surface of the Ross Ice Shelf at Moore’s Bay. The broad sky coverage is specific to the Moore’s Bay site, providing capabilities to observe explosive sources from unknown directions. The ARIANNA architecture is designed to measure the angular direction to within 4 degrees for every neutrino candidate, which too plays an important role in the pursuit of multi-messenger observations of astrophysical sources. The sea level location reduces the impact of a potentially serious background associated with the cores of cosmic ray air showers striking the ice surface, generating radio pulses which are similar to those expected from neutrino events. Reflecting layers at the bottom or within the ice sheet (which are known to exist in thick ice sheets) might create a troublesome rate of background events, provided the reflection coefficients are large enough, that arrive at the detector from the same directions as neutrinos.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Cosmic rays; Cosmology; Glaciers; Ice; Neutrons; Particle detectors; Telescopes